2000
DOI: 10.1152/ajpcell.2000.278.5.c998
|View full text |Cite
|
Sign up to set email alerts
|

IP3 receptors, IP3 transients, and nucleus-associated Ca2+ signals in cultured skeletal muscle

Abstract: Inositol 1,4,5-trisphosphate (IP(3)) receptors (IP(3)R) and ryanodine receptors (RyR) were localized in cultured rodent muscle fractions by binding of radiolabeled ligands (IP(3) and ryanodine), and IP(3)R were visualized in situ by fluorescence immunocytological techniques. Also explored was the effect of K(+) depolarization on IP(3) mass and Ca(2+) transients studied using a radio-receptor displacement assay and fluorescence imaging of intracellular fluo 3. RyR were located in a microsomal fraction; IP(3)R w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

19
154
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(173 citation statements)
references
References 38 publications
19
154
0
Order By: Relevance
“…Similar observations have been recorded in endothelial cells stimulated with thrombin (Ikeda et al, 1996). The cytoplasmic calcium signals induced by thrombin probably result from calcium release from the sarcoplasmic reticulum via IP3R, which is localized in a cross-striated pattern in differentiated myotubes but is not present in young myotubes (Jaimovich et al, 2000). These results are in agreement with the fact that we visualized IP3R in a cross-striated pattern in sarcoplasmic areas where striations were forming.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar observations have been recorded in endothelial cells stimulated with thrombin (Ikeda et al, 1996). The cytoplasmic calcium signals induced by thrombin probably result from calcium release from the sarcoplasmic reticulum via IP3R, which is localized in a cross-striated pattern in differentiated myotubes but is not present in young myotubes (Jaimovich et al, 2000). These results are in agreement with the fact that we visualized IP3R in a cross-striated pattern in sarcoplasmic areas where striations were forming.…”
Section: Discussionsupporting
confidence: 91%
“…in the sarcoplasm, in accordance with a previous study showing more radiolabeled IP3 binding in the nuclear than in the microsomal fraction in cultured rat myotubes (Jaimovich et al, 2000). Calcium signals in nuclei can then result from a cytoplasmic wave by passive diffusion through the nuclear pore complex and/or from calcium released from the nuclear envelope pool via IP3R located on the inner nuclear membrane (Rogue and Malviya, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…Since the T-system serves as source of inositol-trisphosphate (Carrasco et al, 1988;Volpe et al, 1986), which can trigger Ca 2+ -waves, the T-system could be shared at the regulation of the perinuclear Ca 2+ -release (Jaimovich et al, 2000;Powell et al, 2001) in those muscle fiber regions where the nuclei are far a way from myofibrils.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, IP 3 receptors were demonstrated to be preferentially present in the nuclear fraction of cultured rat myotubes [13]. Elevations in extracellular K + concentration were shown to cause a biphasic increase in intracellular Ca 2+ concentration ([Ca 2+ ]).…”
Section: Introductionmentioning
confidence: 99%
“…Elevations in extracellular K + concentration were shown to cause a biphasic increase in intracellular Ca 2+ concentration ([Ca 2+ ]). Detailed analysis revealed that the first increase was fast and associated with contraction, whereas the second increase, which was most prominent in the nuclei, was slow, mediated by IP 3 and responsible for the activation of the transcription factor CREB (cAMP response element-binding protein; [13][14][15]). Similarly, a Ca 2+ ionophore, known to cause a sustained increase in intracellular [Ca 2+ ], was found to increase the activity of the transcription factor NFAT (nuclear factor of activated T cells), in a primary culture of rabbit skeletal muscle [16,17].…”
Section: Introductionmentioning
confidence: 99%